Business Competence of Information Technology Professionals: Conceptual Development and Influence on IT–Business Partnerships1 - Bassellier, Geneviève; Benbasat, Izak (MIS Quarterly, 2004)
This research aims at improving our understanding of the concept of business competence of information technology professionals and at exploring the contribution of this competence to the development of partnerships between IT professionals and their business clients. Business competence focuses on the areas of knowledge that are not specifically IT-related. At a broad level, it comprises the organization-specific knowledge and the interpersonal and management knowledge possessed by IT professionals. Each of these categories is in turn inclusive of more specific areas of knowledge. Organizational overview, organizational unit, organizational responsibility, and IT–business integration form the organization-specific knowledge, while interpersonal communication, leadership, and knowledge networking form the interpersonal and management knowledge. Such competence is hypothesized to be instrumental in increasing the intentions of IT professionals to develop and strengthen the relationship with their clients. The first step in the study was to develop a scale to measure business competence of IT professionals. The scale was validated, and then used to test the model that relates competence to intentions to form IT-business partnerships. The results support the suggested structure for business competence and indicate that business competence significantly influences the intentions of IT professionals to develop partnerships with their business clients.